2019
DOI: 10.1029/2018gl081776
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Strong El Niño and La Niña Events on the North Atlantic

Abstract: The impact of strong La Niña events on January–February North Atlantic mean sea level pressure is unknown, as these events have never been observed. Using large ensembles from the Met Office decadal prediction system, examples of strong La Niña events are simulated and the Atlantic response to these is found to be a positive North Atlantic Oscillation. This is very different to the wavelike response observed and simulated for strong El Niño events. The reason for this difference is traced to the fact that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 55 publications
9
84
0
Order By: Relevance
“…Deser et al 2017;Ayarzagüena et al 2018;Weinberger et al 2019) and others claiming asymmetry (e.g. Trascasa-Castro et al 2019;Hardiman et al 2019; Jiménez-Esteve and Domeisen 2019). The actual "linearity" of the ENSO-NAE teleconnection thus remains unresolved, and addressing this issue is the primary objective of this study.…”
Section: Introductionmentioning
confidence: 93%
“…Deser et al 2017;Ayarzagüena et al 2018;Weinberger et al 2019) and others claiming asymmetry (e.g. Trascasa-Castro et al 2019;Hardiman et al 2019; Jiménez-Esteve and Domeisen 2019). The actual "linearity" of the ENSO-NAE teleconnection thus remains unresolved, and addressing this issue is the primary objective of this study.…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies have explored the response of the stratosphere to extreme ENSO activity (Christiansen et al, 2016;Dunkerton, 2016;Avery et al, 2017;Palmeiro et al, 2017;Varotsos et al, 2017). Rao and Ren (2016b) and Hardiman et al (2019) reported the nonlinear responses of the NH stratosphere to ENSO events of different intensities in winter. In contrast, Zhou et al (2018) found more linear responses to El Niño intensity change in early spring.…”
mentioning
confidence: 99%
“…There are statistically significant RWS anomalies in the tropical Atlantic below 15 • N. Wet and dry composites for both Z250 and RWS show qualitative linearity of these anomalies. Although the RWS has a quadratic form, Hardiman et al (2019) also showed linearity in the RWS, to different ENSO strengths. Figure 2d shows the GPCP precipitation regression.…”
Section: Observational Analysesmentioning
confidence: 96%
“…Although the RWS has a quadratic form, Hardiman et al . () also showed linearity in the RWS, to different ENSO strengths.…”
Section: Observational Analysesmentioning
confidence: 99%